2012
DOI: 10.1007/s11434-012-5507-2
|View full text |Cite
|
Sign up to set email alerts
|

Satellite orbit determination by transfer with differenced ranges

Abstract: The original idea of orbit determination called "determination of satellite orbit by transfer" was proposed by the National Time Service Center, Chinese Academy of Sciences. It shows that the system is very stable and the orbit determination accuracy is improved greatly. A new observation mode called "differenced ranges between master station and slave stations by transfer" is introduced. It is the development of "determination of satellite orbit by transfer". In principle, the differenced ranges between maste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The precision of the station coordinates is better than 5 mm, while the corresponding precision of baselines is better than 1 cm [2]. The residual of POD with ranging data by transfer with 1 day arc is 6.5 cm, while the residual of POD with differenced ranges by transfer with 1 day arc is 9.4 cm [2]. The observation precision of differenced ranges by transfer is 16.5 mas on the baseline of 1177451.2031 m between Lintong and Shanghai.…”
Section: Principle Of Differenced Ranges Between Master Station and Smentioning
confidence: 91%
See 3 more Smart Citations
“…The precision of the station coordinates is better than 5 mm, while the corresponding precision of baselines is better than 1 cm [2]. The residual of POD with ranging data by transfer with 1 day arc is 6.5 cm, while the residual of POD with differenced ranges by transfer with 1 day arc is 9.4 cm [2]. The observation precision of differenced ranges by transfer is 16.5 mas on the baseline of 1177451.2031 m between Lintong and Shanghai.…”
Section: Principle Of Differenced Ranges Between Master Station and Smentioning
confidence: 91%
“…The detailed principle of differenced ranges between master station and slave stations by transfer can be referred to [2].…”
Section: Principle Of Differenced Ranges Between Master Station and Smentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that POD and prediction of precision using the combination of the "receiving own stationdisseminated signals" data (ranging data) and the "differenced ranges between masterslave stations" data is higher than one using only ranging observation Yang et al, 2012). It has been shown that POD and prediction of precision using the combination of the "receiving own stationdisseminated signals" data (ranging data) and the "differenced ranges between masterslave stations" data is higher than one using only ranging observation Yang et al, 2012).…”
Section: Introduction the Space Segment Of The China Satmentioning
confidence: 99%